Global asymptotic properties for a Leslie-Gower food chain model - Andrei Korobeinikov; William T. Lee (Mathematical Biosciences and Engineering)
We study global asymptotic properties of a continuous timeLeslie-Gower food chain model. We construct a Lyapunov function whichenables us to establish global asymptotic stability of the uniquecoexisting equilibrium state.